PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT, LEVERAGE DAN ACTIVITY TERHADAP KINERJA PERUSAHAAN - Anabella, Anabella; Siregar, Anitaria (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2022)
The purpose of this research is to investigate the the influence of economic, environment and social part of sustainability report disclosures, leverage and activity towards the firm performance. The sample of this research is 15 company with sub- sector mining, agricultural and energy which registered in Indonesia Stock Exchange from period 2017 – 2019. This research uses IBM SPSS 27. The result shown that social part of sustainability report disclosures and activity influence the firm performance. Economic and environment part of sustainability report disclosures and leverage do not influnce the firm performance.